Communism, culture and society in the 20th century. - Communist Party of Great Britain; Archive Trust of the Communist Party of Great Britain (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2021)
This collection contains documents compiled by the Communist Party of Great Britain’s (CPGB) National Cultural Committee. The National Cultural Committee (NCC) was established in 1947 and functioned as an advisory panel for the Executive Committee. It aimed to develop policy related to the sphere of culture and the arts for the consideration of the Executive Committee.
Date range: 1900-1999.
Keywords: Communism -- Great Britain -- History -- 20th century -- Sources; Communism and culture -- Great Britain; Communist Party of Great Britain. -- National Culture Committee -- Records and correspondence